Premenstrual dysphoric disorder: brief review - Demarque, Renata (2013)
While most women of reproductive age suffer from some degree of premenstrual symptoms, usually involving mood changes andsomatic complains, only a small percentage have the more severe form, known as premenstrual dysphoric disorder, which causesmarked impairment in the patients life and in the life of her family. This paper will help the clinician to recognize, understand andtreat this disorder